Acute and 28 Days Repeated Oral Toxicity Studies of A Siddha Drug Kalamega Narayana Chendooram in Kodiveli Verpattai Chooranam on Wistar Albino Rats - Ramkumar, G G (International Journal of Pharmaceutical & Biological Archive, 2014)
Acute and 28 Days Repeated Oral Toxicity Studies of A Siddha Drug Kalamega Narayana Chendooram in Kodiveli Verpattai Chooranam on Wistar Albino Rats